Paper and light : luminous drawings - Brooks, Julian, 1969-; Sullivan, Michelle (Conservator) (J. Paul Getty Museum, 2024)
"Discusses the history of extraordinary light effects on the surface of and through paper in drawings from the Renaissance to today"-- Provided by publisher.
"This publication is issued on the occasion of the exhibition Paper and Light: Luminous Drawings, on view at the J. Paul Getty Museum at the Getty Center, Los Angeles, from October 15, 2024, to January 19, 2025"--Colophon.
Keywords: Shades and shadows in art -- Exhibitions.; Light in art -- Exhibitions.; Drawing, European -- Exhibitions.; Drawing -- Technique -- Exhibitions.; Paper -- Europe -- Exhibitions.; Ombres dans l'art -- Expositions.; Lumière dans l'art -- Expositions.; Dessin européen -- Expositions.; Dessin -- Technique -- Expositions.; ART / General; Electronic books.